Design and implementation reversible multiplexer using quantum-dot cellular automata approach - Noora H. Sherif; Mohammed Hussien Ali; Najim Abdallah Jazea (Bulletin of Electrical Engineering and Informatics, 2022)
Rapid progress in the field of nanotechnology includes using quantum dot-cellular automata (QCA) as a replacement for conventional transistor-based complementary metal oxide semiconductor (CMOS) circuits in the construction of nano-circuits. Due to ultra low thermal dissipation, rapid clocking, and extremely high density, the QCA is a rapidly growing field in the nanotechnological field to inhibit the field effect transistor (FET)-based circuit. This paper discusses and evaluates two multiplexer (MUX) architectures: an innovative and effective 4×1 MUX structure and an 8×1 MUX structures using QCA technology. The suggested architectural designs are constructed using the Fredkin and controlled-NOT (CNOT) gates. These constructions were designed to simulate using tool QCA designer 2.0.3. The 591 and 1,615 cells would be used by the 4×1 and 8×1 QCA MUX architectures, respectively. The simulation results demonstrate that, when compared to the previous QCA MUX structures, the suggested QCA MUX designs have the best clock latency performance and use of different gate types.